PENGARUH DAKWAH TERHADAP MASYARAKAT MINORITAS MUSLIM - Husna Sari Siregar; Ahmad Dahlan Pohan (Studia Sosia Religia, 2021)
Islamic teaching is a perfect and comprehensive conception, because it covers all aspects of human life, both worldly and ukhrawi. Islam theologically, is a teaching system that is divine and transcendent. Meanwhile, from the sociological aspect, Islam is a phenomenon of civilization, culture, and social realities and human life. One of the religious activities directly used to socialize Islamic teachings for its adherents is da'wah activity. This activity is carried out either through oral writing or by real action. The method used by the researcher is descriptive qualitative method with the approach of religious phenomonology, which is a separate discipline that studies religion as a fact or event that can be objectively observed. The results of the da'wah obtained are that the Muslim community is not affected and leaves the religion of Islam (apostasy) from the environment, inviting / teaching future generations to deepen the knowledge of Islam. The aim of this research is to create a harmonious life between religions, and for Muslims, they must deepen their knowledge of Islam so that they are not easily influenced.